Protein Intake of Growing Indigenous Chickens on Free-Range and Their Response to Supplementation - Kingori, A.M.; Tuitoek, J.K.; Muiruri, H.K.; Wachira, A.M.; Birech, E.K. (International Journal of Poultry Science, 2007)
Three experiments were conducted to determine protein intake and the response of growing indigenous chickens to protein supplementation under free-ranging conditions. In the first experiment, data were collected from which a model was designed to estimate daily feed intake of free-ranging indigenous chicken from the Crop Contents (CC). The second experiment applied the model under on-farm conditions to estimate feed intake of free-ranging growers. Crude Protein (CP) intake was calculated as the product of crude protein concentration and total intake of feed. Results indicated that the mean protein level of CC was 11.2%, Dry Matter Intake (DMI) of free-ranging growers was 78.3g/grower/day and the mean Crude Protein Intake (CPI) was about 8.5 g. In order to establish the response of the growers to protein supplementation in an on-farm set-up, the third experiment provided protein supplements at 0, 1.6, 3.2 and 4.8 g CP/bird/day. Daily CPI for each of the four supplementary groups was calculated to be 8.5, 10.1, 11.7 and 13.3 g/bird. Growth rate and body weight increased with increasing protein supplementation up to 3.2 g CP/bird/day. Higher levels of protein supplementation did not significantly increase growth rate or body weight. Therefore, the CP requirement for growing indigenous chickens on free-range was estimated at 11.7 g/day. Protein supplementation of 3.2 g/bird/day to a growing indigenous chicken on free-range is therefore mandatory for optimum growth.